Sperm quality of drones of Apis mellifera L. selected for royal jelly production (Acta Scientiarum. Animal Sciences, 2025)
Royal jelly is importance within the hive colony for feed and regulation of sex hormones. The objective of this study was to evaluate the reproductive characteristics of drones with D and E alleles (high production of royal jelly), compared with at least one F or G alleles (lower production of royal jelly). Drones were created from selected colonies and an analysis of the semen quality and weight of each drone was performed. The colonies with alleles D and E had a higher drone production but with lower. However, there was no interference from the alleles on the sperm quality of the drone, which presented: survival 88.38%, volume 1.2 µL, mass motility 5. The abnormalities were bent tail, headless and tailless sperm, and bifurcated tail. The alleles D and E influenced the weight and quantity of the drones but not their sperm quality.